Altered Sexual Behavior in Dopamine Transporter (DAT) Knockout Male Rats: A Behavioral, Neurochemical and Intracerebral Microdialysis Study - Sanna, Fabrizio; Bratzu, Jessica; Serra, Maria Pina; Leo, Damiana; Quartu, Marina; Boi, Marianna; Espinoza, Stefano; Gainetdinov, Raul R.; Melis, Maria Rosaria; Argiolas, Antonio (Frontiers in Behavioral Neuroscience, 2020)
Central dopamine plays a key role in sexual behavior. Recently, a Dopamine-Transporter knockout (DAT KO) rat has been developed, which displays several behavioral dysfunctions that have been related to increased extracellular dopamine levels and altered dopamine turnover secondary to DAT gene silencing. This prompted us to characterize the sexual behavior of these DAT KO rats and their heterozygote (HET) and wild type (WT) counterparts in classical copulatory tests with a sexually receptive female rat, and to verify if and how the acquisition of sexual experience changes along five copulatory tests in these rat lines. Extracellular dopamine and glutamic acid concentrations were also measured in the dialysate obtained by intracerebral microdialysis from the nucleus accumbens (Acb) shell of DAT KO, HET and WT rats, which underwent five copulatory tests, when put in the presence of an inaccessible sexually receptive female rat and when copulation was allowed. Markers of neurotrophism (BDNF, trkB), neural activation (Δ-FosB), functional (Arc and PSA-NCAM) and structural synaptic plasticity (synaptophysin, syntaxin-3, PSD-95) were also measured in the ventral tegmental area (VTA), Acb (shell and core) and medial prefrontal cortex (mPFC) by Western Blot assays. The results indicate that sexual behavior of DAT KO versus HET and WT rats shows peculiar differences, mainly due to a more rapid acquisition of stable sexual activity levels and to higher levels of sexual motivation and activity. These differences occurred with differential changes in dopamine and glutamic acid concentrations in Acb dialysates during sexual behavior, with lower increases of dopamine and glutamic acid in DAT KO versus WT and HET rats, and a lower expression of the markers investigated, mainly in the mPFC, in DAT KO versus WT rats. Together these findings confirm a key role of dopamine in sexual behavior and provide evidence that the permanently high levels of dopamine triggered by DAT gene silencing cause alterations in both the frontocortical glutamatergic neurons projecting to the Acb and VTA and in the mesolimbic dopaminergic neurons, leading to specific brain regional changes in trophic support and neuroplastic processes, which may have a role in the sexual behavior differences found among the three genotypes.